Predictors and Clinical Outcomes of Vasoplegia in Patients Bridged to Heart Transplantation With Continuous‐Flow Left Ventricular Assist Devices. Issue 22 (19th November 2019) - Asleh, Rabea; Alnsasra, Hilmi; Daly, Richard C.; Schettle, Sarah D.; Briasoulis, Alexandros; Taher, Riad; Dunlay, Shannon M.; Stulak, John M.; Behfar, Atta; Pereira, Naveen L.; Frantz, Robert P.; Edwards, Brooks S.; et al.
Abstract : Background: The presence of a durable left ventricular assist device (LVAD) is associated with increased risk of vasoplegia in the early postoperative period following heart transplantation (HT). However, preoperative predictors of vasoplegia and its impact on survival after HT are unknown. We sought to examine predictors and outcomes of patients who develop vasoplegia after HT following bridging therapy with an LVAD. Methods and Results: We identified 94 patients who underwent HT after bridging with continuous‐flow LVAD from 2008 to 2018 at a single institution. Vasoplegia was defined as persistent low vascular resistance requiring ≥2 intravenous vasopressors within 48 hours after HT for >24 hours to maintain mean arterial pressure >70 mm Hg. Overall, 44 patients (46.8%) developed vasoplegia after HT. Patients with and without vasoplegia had similar preoperative LVAD, echocardiographic, and hemodynamic parameters. Patients with vasoplegia were significantly older; had longer LVAD support, higher preoperative creatinine, longer cardiopulmonary bypass time, and higher Charlson comorbidity index; and more often underwent combined organ transplantation. In a multivariate logistic regression model, older age (odds ratio: 1.08 per year; P =0.010), longer LVAD support (odds ratio: 1.06 per month; P =0.007), higher creatinine (odds ratio: 3.9 per 1 mg/dL; P =0.039), and longer cardiopulmonary bypass time (odds ratio: 1.83 per hour; P =0.044) were independent predictors of vasoplegia. After mean follow‐up of 4.0 years after HT, vasoplegia was associated with increased risk of all‐cause mortality (hazard ratio: 5.20; 95% CI, 1.71–19.28; P =0.003). Conclusions: Older age, longer LVAD support, impaired renal function, and prolonged intraoperative CPB time are independent predictors of vasoplegia in patients undergoing HT after LVAD bridging. Vasoplegia is associated with worse prognosis; therefore, detailed assessment of these predictors can be clinically important.